Multi-Objective Optimization of Energy, Exergy, Exergoeconomic Analyses a Double-Pessure Flash-Binary Geothermal Power System Using Zeotropic Working Fluid - Arivalagan Pugazhendhi; Van Vang (Advances in Engineering and Intelligence Systems)
Global warming due to greenhouse emission is the most annoying problem for sustaining life on earth. This paper combines a geothermal system with an organic Rankine cycle (ORC). Comprehensive thermodynamic and thermoeconomic analyses are employed to estimate the system performance and generate 3083 kW net power with 64.79% exergy efficiency and 3.51 years payback period. Parametric study is conducted to study the effect of some main parameters variation on the proposed system performance. Regarding the parametric study results, the vapor generator’s evaporation temperature has the highest effect on the system exergy destruction. The second separator inlet pressure influences the net power production and exergy efficiency higher than other parameters. Then, the net present value is calculated for four geofluid and electricity costs. The electricity sale cots enhancement of about 33% increases the net profit by about 78.29%, and increasing the geofluid prices by about 38.4% declines the net profit of the proposed system by about 19.5%. Two multi-objective optimization scenarios are employed to optimize the energy efficiency with the payback period and exergy efficiency with the payback period. The optimization results indicate that the 20.63% energy efficiency with 3.58 years payback is the first scenario optimum point. The 65.53% exergy efficiency with 3.47 years payback period is the second scenario’s optimum point.